"Creating the Old" in Literature. (1st September 2016) - Shaogong, Han; Chenmei, Xu
Abstract : In this passionate think-piece, the novelist Han Shaogong, whom many accredit as the founder of "root-seeking literature, " argues for a balanced approach to tradition and innovation in contemporary Chinese literature, citing the dangers of cheap novelty and recalcitrant conservatism. He points to a thriving cultural space where the new and old are intractably interwoven and capable of generating the most important literary virtue of all: quality itself .